Memasyaratkan Sholawat Nariyah Di Bumi Nusantara - Holidi, Ahmad Farhan; Surur, Miftahus (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2019)
The tradition of reading the Nariyah prayer individually and in congregation has taken root in the midst of the community especially in Situbondo district, in every corner of the city and remote villages even though every day is not empty from reciting the 4444 shalawat nariyah individually and in congregation, so that Situbondo district is the term "BUMI SHALAWAT NARIYAH". At first Jam'iyah this prayer was commanded by KH Ahmad Sufyan Miftahul Arifin (Situbondo) and KH Muhammed bin Imam Gunungsari (Madura) then continued by his students both namely KHR Moh Kholil As'ad Syamsul Arifin he was the son of KH As' ad the mediator in the formation of Jam'iyah Nahdhatul Ulama (NU) as well as the Indonesian National hero. And today the recitation of the Nariyah prayer has spread widely in various regions, in East Java, Bali, Kalimantan, DKI Jakarta, DIY Yogyakarta to foreign countries such as Malaysia and Singapore all thanks to the help of Allah SWT with the hope that Allah will flow to us all drop by drop from the ocean of God's grace which was bestowed upon the Prophet Muhammad.